Pengaruh Label Halal Kualitas Produk Dan Keberagaman Varian Terhadap Keputusan Pembelian Pada Produk Perawatan Kulit Scarlett Di Toko Amadeus Beauty Kota Jambi - Rifani Syahara; Titin Agustin Nengsih; Nurlia Fusfita (Jurnal Development, 2024)
This research aims to determine the influence of the halal label, product quality and variant diversity on consumer purchasing decisions for Scarlett Whitening products from Toko Amadeus Cosmetics Jambi, this research is quantitative. The sample used was 100 respondents who were consumers of the Amadeus Cosmetics Shop in Jambi. Based on the research results, there is one variable that does not have a significant effect on the purchasing decisions of Amadeus Cosmetic Shop Jambi consumers, namely the Product Quality variable (X2), while the halal label variables (X1) and variant diversity (X3) have a positive and significant effect on consumer purchasing decisions for Scarlett Products. Whitening Amadeus Cosmetics Shop Jambi. Simultaneously there is a significant influence between the halal label, product quality and variant diversity with an Adjusted R Square (R2) value of 52.1% and the remaining 57.9% is influenced by other variables outside this research.